Ice planet adventure - Stilton, Geronimo; Dami, Elisabetta (Stilton, Geronimo. Spacemice, 2015)
Friends of the spacemice have disappeared on a strange ice planet, Polarix! Geronimo Stiltonix and his crew are called to search for them. When the spacemice arrive on Polarix, they're surprised at the inhabitants -- cute little aliens that look like colorful fuzz balls! But are these creatures as harmless as they look?